Development and optimization of an in-house heterologous ELISA for detection of prednisolone drug in enzyme conjugates using spacers - Kumar, Dinesh; Oberoi, Harinder Singh; Singh, Harpal; Shrivastav, Tulsidas G.; Bhukya, Prudhvi Lal; Kumari, Mansi; Koner, Bidhan Chandra; Sonkar, Subash Chandra (Frontiers in Immunology, 2023)
The introduction of spacers in coating steroid protein complex and / or enzyme conjugates or immunogen is known to exert an influence on the sensitivity of steroid enzyme immunoassays. We investigated the impact of different homobifunctional spacers, ranging in atomic length from 3 to 10, on the sensitivity and specificity of prednisolone (PSL) enzyme immunoassays. In this study, four homo-bifunctional spacers namely; carbohydrazide (CH), adipic acid dihydrazide (ADH), ethylene diamine (EDA) and urea (U) were incorporated between PSL and HRP for preparing the enzyme conjugate with an aim to improve the sensitivity of the assay without compromising assay specificity. The assays were developed using these enzymes conjugate with antibody raised against PSL-21-HS-BSA immunogen. The sensitivity of the PSL assays after insertion of bridge in enzyme conjugate were 1.22 ng/mL, 0.59 ng/mL, 0.48 ng/mL and 0.018 ng/mL with ADH, CH, EDA and urea as spacer respectively. Among all four combinations PSL-21-HS-BSA-antibody with PSL-21-HS-U-HRP-enzyme conjugate gave better sensitivity and less cross-reaction. The percent recovery of PSL from the exogenously spiked human serum pools was in the range of 88.32-102.50 %. The intra and inter assay CV% was < 8.46%. The PSL concentration was estimated in the serum samples of patients on PSL treatment. The serum PSL values obtained by this method correlated well with the commercially available kit (r 2 = 0.98). The present study, suggests that the nature of the spacer is related to assay sensitivity and not the spacer length.